Sacred Traditions in Sacred Places - Khakdodov, Safar (The Christensen Fund, The Aga Khan Humanities Project, 2005)
Donation from OSI-Budapest Arts and Culture Program. Duration: 00:55:00 The film captures some of the diverse religious and cultural practices among the Ismailis of the Badadkhshan in Tajikistan. These traditions are practiced in different parts of Badadkhshan with nuanced differences. All reflect an adherence to the Ismaili interpretation of Islam.